2010
DOI: 10.1080/02701960903578345
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Service Learning: To Promote Active Aging, and Occupational Therapy Gerontology Practice

Abstract: Americans are living longer, and the meaning of age has changed, particularly for Boomers and seniors. These demographic changes have economic and social ramifications with implications for health care, including rehabilitation services, and health science education. Service learning is an experiential learning pedagogy that integrates traditional higher education with structured active learning experiences. This article reports on one intergenerational service learning program spanning 3 years. It was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
2
28
0
2
Order By: Relevance
“…The findings of this study further corroborated those of Adams and Wonnacott 25 who found that a rural service learning experience afforded students with opportunities for development of professional and personal competencies, corresponding with findings relating to developing personal capacities in this study. Other studies among occupational therapy students have also drawn similar conclusions regarding the value of service learning experiences 7,8,9 . The results of this study are also congruent with findings in service learning literature outside of the profession of occupational therapy that suggest positive contributions to students' academic, professional and personal growth 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The findings of this study further corroborated those of Adams and Wonnacott 25 who found that a rural service learning experience afforded students with opportunities for development of professional and personal competencies, corresponding with findings relating to developing personal capacities in this study. Other studies among occupational therapy students have also drawn similar conclusions regarding the value of service learning experiences 7,8,9 . The results of this study are also congruent with findings in service learning literature outside of the profession of occupational therapy that suggest positive contributions to students' academic, professional and personal growth 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 55%
“…Other studies among occupational therapy students have also demonstrated that participation in service learning (not necessarily in rural areas) enhanced students' knowledge of the scope of occupational therapy 8 and their skills in working in community settings 7 . The findings of this study further corroborated those of Adams and Wonnacott 25 who found that a rural service learning experience afforded students with opportunities for development of professional and personal competencies, corresponding with findings relating to developing personal capacities in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive changes in students' critical thinking were reported in (Astin and Sax, 1998;Osborne et al, 1998;Sedlak et al, 2003;Beling, 2004;Reynolds, 2005;Liang En et al, 2011b) studies with improvements in engagement, curiosity and reflective practice in (Beling, 2003;Ngai, 2006;Casey & Murphy, 2008;Faria et al, 2010) others. While many studies (Poulin et al, 2006;McWilliams et al, 2008;Brown, 2009;Horowitz et al, 2010;Krout et al, 2010) reported that students valued SL experiences this outcome may indicate "little more than that the students liked the innovation" (Abassi & Smith, 1999, p. 1265) and we must be wary of what Norman calls "me-too" research (Norman, 2006, p. 1). In these instances another form of experiential learning may have been equally, or indeed more suited, to achieve desired learning outcomes.…”
Section: )mentioning
confidence: 97%
“…people who are homeless, people with HIV, people experiencing poverty and health inequities, etc. (Burrows et al, 1999;Elam et al, 2003;Bentley & Ellison, 2005;Casey & Murphy, 2008;Amerson, 2010;Horowitz et al, 2010;McMenamin et al, 2010;Green et al, 2011;Liang En et al, 2011b;Mitschke & Petrovich, 2011;Reading & Padgett, 2011;Schindler, 2011). Working in partnership with the "different other" appeared to help students develop a deeper appreciation of the vulnerabilities that marginalized segments of the population experience and nurture a purposeful sense of social responsibility.…”
Section: )mentioning
confidence: 99%